DiGRA India - YouTube - DiGRA India (Youtube, 2020)
The Digital Games Research Association (popularly known as DiGRA) is “ the premiere international association for academics and professionals who research digital games and associated phenomena. It encourages high-quality research on games, and promotes collaboration and dissemination of work by its members” (DiGRA website). DiGRA was founded in 2003 and today, we are proud to inaugurate its Indian chapter almost two decades later. India’s ludic history is rich and ancient; the world’s longest epic The Mahabharata has as one of its crucial episodes, a dice-game match and the consensus among games historians is that Chess originated from chaturanga, the four-handed strategy game. Today, India is a major Cricketing nation and has a large presence in the Olympic games but it is also emerging as an important centre for digital gaming, particularly mobile gaming. Digital games have also emerged as platforms of cultural contentions, controversies, creativity and discussions around social issues. From a sole games researcher in 2001 to about a hundred odd in different parts of the country, research in digital games has grown significantly. Starting off as Games Studies India adda, this platform for discussing all issues relating to gaming cultures is now poised to take a new turn as DiGRA India. As there is no other platform that facilitates research on non-digital games as well on a regular basis, DiGRA India aims to provide a space for discussions on all kinds of games and game culture(s).
Keywords: 1-Jeux vidéo; 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé